Canine infection by Ehrlichia canis and Anaplasma platys in the semiarid region of Brazil: frequency and molecular characterization - Lucilene Santos Silva; Flaviane Alves de Pinho; Lidiany Viana Pires; Juliana Fortes Vilarinho Braga; Thamires Carvalho da Luz; Francisco de Assis Leite Souza; Maria do Socorro Pires e Cruz; João Pessoa Araújo Júnior; Silvana Maria Medeiros de Sousa Silva (Revista Brasileira de Saúde e Produção Animal)
ABSTRACT Canine monocytic ehrlichiosis and canine thrombocytic anaplasmosis, caused by Ehrlichia canis and Anaplasma platys, are endemic diseases in Brazil. This study aimed to determine the occurrence of these pathogens in 224 dogs at a Veterinary Teaching Hospital in Piauí, northeastern Brazil. DNA samples were analyzed using PCR assays for E. canis and A. platys, followed by sequencing and phylogenetic analysis. Clinical data were collected from medical records. A total of 17.9% of the dogs (40/224) were positive for E. canis, 30.8% (69/224) for A. platys, and 16.5% (37/224) for both. Ticks were present in 50% of the dogs infected with E. canis, 59.4% with A. platys, and 62.2% with both bacteria. Common clinical and laboratory changes included lymphadenopathy, anemia, thrombocytopenia, hyperglobulinemia, and hypoalbuminemia. The partial 16S rDNA gene sequences of E. canis and A. platys from dogs in Piauí showed 99% to 100% and 99.74% identity to reference sequences from different regions of Brazil and other countries in GenBank, respectively. Phylogenetic analysis revealed that the sequences were grouped into their respective clades. This study represents the first molecular survey and phylogenetic characterization of these bacteria in dogs in the semiarid region of Piauí.